(untitled) (Proceedings of the International Conference on Public Health, 2024)
Work stress is a common phenomenon experienced by workers, including teachers, that can result in feelings of pressure and other adverse symptoms. The purpose of this study was to identify the factors associated with work stress among teachers in Public Special Schools in Padang City in 2022, using a quantitative cross-sectional design. A total sampling technique was used to recruit 32 teachers who are not have special school background and met the inclusion and exclusion criteria. The data were collected using a questionnaire and analyzed using SPSS software and the chi-square test. The results of the study showed that 62.5% of the teachers experienced heavy work stress, with environmental, organizational, and individual factors all contributing to this stress. Specifically, 65.5% of teachers experienced risky environmental factors, 62.5% experienced risky organizational factors, and 65.6% experienced individual risk factors. The bivariate analysis indicated that there was a statistically significant relationship between work stress and environmental factors (p = 0.035), organizational factors (p = 0.014), and individual factors (p = 0.005) among teachers in Special Schools in Padang City in 2022. These findings suggest that school should update and improve teaching and learning facilities and work collaboratively to create a conducive work environment. Additionally, institutions should recognize and reward teachers for their passion and giving motivation while teaching.